Enhancing Student Motivation in Art Lessons through Gamification - Usmonov Umid Farxodovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: Gamification, the application of game design elements in non-game contexts, has emerged as an effective strategy to increase student engagement and motivation in education. In art lessons, gamified activities—such as interactive challenges, point-based rewards, and collaborative competitions—can stimulate creativity, foster active participation, and promote deeper understanding of artistic concepts. This paper explores the potential of gamification to enhance students’ intrinsic and extrinsic motivation in secondary school art classes. It also examines practical strategies for integrating gamified methods, highlights benefits for learning outcomes, and addresses challenges in implementation. By leveraging gamification, educators can create dynamic and interactive art learning environments that nurture creativity, collaboration, and sustained interest in the subject.